2018
DOI: 10.3390/ijerph15112524
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Indoor PM2.5 Concentration in Gers Using Coal Stoves in Ulaanbaatar, Mongolia

Abstract: Coal combustion in ger areas is the main source of ambient air pollution in Ulaanbaatar (Mongolia). This study determined the characteristics of indoor PM2.5 concentrations in gers using coal stoves during winter. The study population consisted of 60 gers in the Chingeltei district of Ulaanbaatar. The indoor particle number concentration (PNC) in each ger was measured using a Dylos DC1700 particle counter for 24 h in January and February 2016. The PNC by Dylos was converted into the mass concentration using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…However, personal exposure showed the highest value from 7:00 to 12:00 (Table 3). Lim et al concluded (2018) that the UB daily profile and the PM 2.5 concentration showed lower values at night-time, while there were increased values in the early morning, and values peaked in noon [37]. Table 3.…”
Section: Personal Exposure and Dosementioning
confidence: 98%
“…However, personal exposure showed the highest value from 7:00 to 12:00 (Table 3). Lim et al concluded (2018) that the UB daily profile and the PM 2.5 concentration showed lower values at night-time, while there were increased values in the early morning, and values peaked in noon [37]. Table 3.…”
Section: Personal Exposure and Dosementioning
confidence: 98%
“…As a consequence of the incomplete combustion in traditional inefficient stoves, coal combustion in Gers is the main source of air pollution not only because of particulate matter but also soil pollution. This makes Ulaanbaatar one of the most polluted cities in the world [26][27][28]. Environmental pollution of the capital city is mainly derived from incomplete coal combustion in Gers, and frequently exceeds 10 times the national permissible level (50 µg/m 3 ) in winter [28].…”
Section: Discussionmentioning
confidence: 99%
“…This makes Ulaanbaatar one of the most polluted cities in the world [26][27][28]. Environmental pollution of the capital city is mainly derived from incomplete coal combustion in Gers, and frequently exceeds 10 times the national permissible level (50 µg/m 3 ) in winter [28]. Therefore, coal combustion emissions may be one of the major sources of metal pollution in Ulaanbaatar soil.…”
Section: Discussionmentioning
confidence: 99%
“…Then, linear regression analysis was performed between the Dylos HAP concentration data in 0.01 ft 3 and the co-located monitor which allowed PM 2.5 concentration measurements in μg/m 3 of sampled air [ 60 , 63 ]. The analysis result showed a strong linear relationship with a conversion factor of PM 2.5 concentration in μg/m 3 = [(6.22) (Dylos PM 2.5 concentrations in 0.01 ft 3 ) (10 −2 )].…”
Section: Materials and Methods Of The Studymentioning
confidence: 99%